2014
DOI: 10.1371/journal.pone.0107207
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Degenerate Nuclei and Development of a SCAR Marker for Flammulina velutipes

Abstract: Flammulina velutipes is one of the major edible mushrooms in the world. Recently, abnormalities that have a negative impact on crop production have been reported in this mushroom. These symptoms include slow vegetative growth, a compact mycelial mat, and few or even no fruiting bodies. The morphologies and fruiting capabilities of monokaryons of wild-type and degenerate strains that arose through arthrospore formation were investigated through test crossing. Only one monokaryotic group of the degenerate strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In the case of Yin et al (2017) , it was shown that strains began to degenerate at the third generation, with their fruiting bodies displaying incomplete growth on the fourth one. Finally Kim et al (2014) , reported slow vegetative growth, tight mycelial pads, and few or no fruiting bodies as some of the symptoms of degraded F. velutipes strains. In line with the above, and particularly the findings of ( Sun et al, 2017 ), this study showed that the density of aerial mycelia, along with their growth rate and biomass, gradually decreased as the degeneration level increased ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Yin et al (2017) , it was shown that strains began to degenerate at the third generation, with their fruiting bodies displaying incomplete growth on the fourth one. Finally Kim et al (2014) , reported slow vegetative growth, tight mycelial pads, and few or no fruiting bodies as some of the symptoms of degraded F. velutipes strains. In line with the above, and particularly the findings of ( Sun et al, 2017 ), this study showed that the density of aerial mycelia, along with their growth rate and biomass, gradually decreased as the degeneration level increased ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…They were not detected in the normal strains in fruiting-impaired degenerative isolates. Kim et al (2014) reported that the symptoms of degenerated F. velutipes strains include slow vegetative growth, a compact mycelial mat, and few, or even no, fruiting bodies. Yin et al (2017) artificially cultured the entomopathogenic mushroom Cordyceps militaris for six generations and observed changes during fruiting-body growth.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there was no significant difference in the mycelial biomass between M1 and M0 ( P > 0.05), but there were significant differences in the mycelial biomasses between M2–M6 and M0 ( P < 0.05) (Figure 2). Thus, the mycelial biomasses of degenerated strains decreased continuously as the subculturing continued, which might result in unsatisfying, and even a lack of, output from degenerated strains (Kim et al, 2014; Chen et al, 2017; Yin et al, 2017). Moreover, we discovered a similar trend between the mycelial growth rate and mycelial biomass as the subculturing continued.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies have reported the use of SCAR markers for edible fungi. For example, they have been used in studies on the color of the fruiting bodies of Agaricus bisporus [ 12 ], Flammulina velutipes [ 13 ] and Hypsizygus marmoreus [ 14 ], the degeneration of Volvariella volvacea strains [ 15 ] and F. velutipes [ 16 ], mushroom disease in Auricularia polytricha [ 17 ], and the mating types of edible fungi [ 18 , 19 ]. These markers have also been used to screen for various traits during breeding.…”
Section: Introductionmentioning
confidence: 99%